Diagnostic value of symptoms and signs for identifying urinary tract infection in older adult outpatients: systematic review and meta-analysis - Gbinigie, OA; Ordonez-Mena, JM; Fanshawe, TR; Pluddemann, A; Heneghan, C (Elsevier, 2018)
Objectives To critically appraise and evaluate the diagnostic value of symptoms and signs in identifying UTI in older adult outpatients, using evidence from observational studies. Methods We searched Medline and Medline in process, Embase and Web of Science, from inception up to September 2017. We included studies assessing the diagnostic accuracy of symptoms and/or signs in predicting UTI in outpatients aged 65 years and above. Study quality was assessed using the QUADAS-2 tool. Results We identified 15 eligible studies of variable quality, with a total of 12,039 participants (range 65–4259), and assessed the diagnostic accuracy of 66 different symptoms and signs in predicting UTI. A number of symptoms and signs typically associated with UTI, such as nocturia, urgency and abnormal vital signs, were of limited use in older adult outpatients. Inability to perform a number of acts of daily living were predictors of UTI: For example, disability in feeding oneself, + ve LR: 11.8 (95% CI 5.51–25.2) and disability in washing one's hands and face, + ve LR: 6.84 (95% CI 4.08–11.5). Conclusions The limited evidence of varying quality shows that a number of symptoms and signs traditionally associated with UTI may have limited diagnostic value in older adult outpatients.